Experience of Perinatal and Neonatal Chikungunya Virus (CHIKV) Infection in a Tertiary Care Neonatal Centre during Outbreak in North India in 2016: A Case Series. (9th June 2018) - Kumar, Surender; Agrawal, Gopal; Wazir, Sanjay; Kumar, Anil; Dubey, Sandeep; Balde, Manish; Yadav, Bir Singh
Abstract: Background: In 2016, there was a massive outbreak of chikungunya in North India. During the epidemic, we observed many neonatal and early infantile cases of chikungunya, with a probable perinatal transmission. Methods: This retrospective study was carried out in a tertiary care neonatal centre between August 2016 and November 2016. Chikungunya virus (CHIKV) infection was detected and confirmed by reverse transcription-polymerase chain reaction (RT-PCR) and/or serology (anti-CHIKV IgM) in mothers and infants. Clinical features and laboratory parameters were recorded. Results: There were 16 cases of confirmed CHIKV infections during the study period. For babies presenting during the neonatal period ( n  = 13), the median age of presentation was 9.5 (range: 3–15) days, whereas for babies (three) presenting after the neonatal period, the median age was between 1 and 3 months. The most common presentation was fever (69%), followed by lethargy (56%) and seizures (50%). Skin manifestations were observed in 25% of the cases, which included maculopapular rashes, bullous lesions and hyperpigmentation over the axilla, perioral and genital areas. None of the cases had any feature of arthritis. Of all the cases included in the study ( n  = 16), RT-PCR for CHIKV was positive in 14 (87.5%), whereas the serum anti-CHIKV IgM antibody test was positive in two (12.5%) cases. Six (37.5%) cases were documented as perinatal CHIKV, as RT-PCR for CHIKV was positive in both mothers and babies. Fifteen babies survived and were discharged in a stable condition with no oxygen requirement and on full feeds. One baby died because of multi-organ failure and catecholamine refractory hypotension. Conclusion: In endemic areas, paediatricians should have a low threshold of suspicion for perinatal or neonatal chikungunya in any infant presenting with signs and symptoms mimicking sepsis, especially with skin manifestations, seizure and/or encephalopathy.